Effect of sunkist orange peel nanoparticle granules on cardiac and aorta histopathology in diabetic rats - Sihotang, Widya Yanti; Putri, Indah Juwita Dwi; Henny, Henny; Suandy, Suandy; Mutia, Maya Sari (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
Sunkist oranges (Citrus sinensis (L.) Osbeck) is rich in anthocyanins (95% of which are represented by cyanidin-3-glucoside and cyanidin-3-6